2019
DOI: 10.1002/jctb.5907
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical fluid extraction for enhancing polyphenolic compounds production from olive waste extracts

Abstract: BACKGROUNDA number of residues are produced during the olive oil extraction process, such as crushed pits, olive leaves, pomace and exhaust olive pomace. In addition, pruning of olive trees results in a huge amount of biomass. All of these lignocellulosic materials constitute a source of energy and chemicals that can be used as raw materials in biorefineries. Among them, antioxidants are of particular interest due to their potential applications in pharmaceutical and food industry.RESULTSSupercritical fluid ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…Recovery of antioxidant phenols from olive pomace has been performed using common organic solvents such as ethanol [ 11 ] or methanol [ 12 ] in an agitated reactor under high pressure and temperature. Olive pomace has also been hydrothermally pretreated by steam explosion [ 13 ] and subcritical fluid extraction [ 14 , 15 ]. New extraction technologies for olive pomace, such as microwave-assisted extraction, ultrasound-assisted extraction with different solvents [ 16 , 17 , 18 , 19 ], and extraction with natural deep eutectic solvents [ 16 ] have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery of antioxidant phenols from olive pomace has been performed using common organic solvents such as ethanol [ 11 ] or methanol [ 12 ] in an agitated reactor under high pressure and temperature. Olive pomace has also been hydrothermally pretreated by steam explosion [ 13 ] and subcritical fluid extraction [ 14 , 15 ]. New extraction technologies for olive pomace, such as microwave-assisted extraction, ultrasound-assisted extraction with different solvents [ 16 , 17 , 18 , 19 ], and extraction with natural deep eutectic solvents [ 16 ] have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been reported on supercritical fluid extraction with or without a cosolvent of phytosterols, essential oils, pigments [ 29 ], and mainly polyphenols from blueberry, cranberry, and raspberry wastes [ 30 ]; wine industry by-products [ 31 ]; pistachio hull [ 32 ]; olive leaves [ 33 ]; and orange, apple, and tomato pomace [ 34 , 35 , 36 , 37 ]. The SFE of polyphenols has been further carried out from olive pomace [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds such as gallic acid, catechin, and epicatechin are notoriously endowed with antioxidants, astringents, and antimicrobial activity. Therefore, such species are subject of increasing interest in various fields such as pharmaceuticals, leather tanning, cosmetics, and the food industry [7][8][9][10][11]. Low-molecular-weight hydroxybenzoic acids and some of their derivatives can be obtained from wood extractives and via induced lignin degradation [12,13].…”
Section: Introductionmentioning
confidence: 99%